Removal of Pb(II) from industrial wastewater by using various natural materials - A review - Mondal, M.K. (My University, 2008)
Lead's history in science, medicine and technology has been overshadowed by its notoriety as a poison in homicides. Lead is viewed as being synonymous with toxicity. Dangerous lead concentration in natural, as well as industrial wastewater, is now a worldwide problem and often referred to as a 20th-21st century calamity. Existing overviews of lead removal include technologies that have traditionally been used (oxidation, precipitation/coagulation/membrane separation) with far less attention paid to adsorption. No previous review is available where readers can get an overview of the sorption capacities of both available and developed sorbents used for lead remediation. Most of the valuable available literature on lead remediation by adsorption has been incorporated. Lead sorption by commercially available carbons and other low-cost adsorbents developed from various natural materials are surveyed and critically reviewed and their sorption efficiency compared. Some commercially available adsorbents are also surveyed. An extensive table summarizes the maximum percentage of Pb(II) uptake, optimum pH, isothermal model fit and thermodynamic parameters of various adsorbents. Some low cost adsorbents prepared from various natural materials are superior including bagasse fly ash, bone powder, sea nodule, olive cake, polymerized banana stem, tea waste, carbons developed from agricultural waste (coconut shell carbon and palm shell carbon), biosorbents (modified lignin and microspore), phosphogypsum and some commercial adsorbents, which included activated carbon, carbon aerogel tested for lead removal come out to be superior.
Keywords: Adsorption; Industrial wastewater effluent; Lead removal; Natural material; Olive cake; Sea nodule